Letter (copy) : Clothing for Spanish refugees - Tewson, Vincent
026-0038-001 INTERNATIONAL HVT/EAB. 9/4/681 11th August 1939. Mr. A. Conley, National Union of Tailors & Garment Workers, Union Chambers, 20, Park Place, LEEDS. 1. Dear Mr. Conley, CLOTHING FOR SPANISH REFUGEES. Many thanks for your letter of the 16th inst., informing me that you have despatched 13 bales of clothing to Cockleshell Siding, Garston, Liverpool, for shipment to Federation Syndicale Internationale, Rouen. I have today been in touch with the Co-operative Wholesale Society Limited, Manchester, and they are arranging for the consignment to be conveyed by one of their steamers in the course of the next week or ten days. Thank you also for sending a list, in duplicate, showing the contents of each bale. This information will be greatly appreciated by the International Federation of Trade Unions who, as you know, are responsible for the distribution of the goods to the refugees. With many thanks for your assistance, and with kind regards, Yours sincerely, Assistant Secretary. 292/946/26/38